2018
DOI: 10.1016/j.ultrasmedbio.2018.03.031
|View full text |Cite
|
Sign up to set email alerts
|

On Patient Related Factors and Their Impact on Ultrasound-Based Shear Wave Elastography of the Liver

Abstract: The aim of the study was to investigate patient-related factors associated with either reliable or poorly reliable measurement results of ultrasound-based shear wave elastography (SWE) of the liver. A total of 188 patients were analyzed prospectively with binary logistic regression using the interquartile range/median as cutoff to define two groups based on reliable and poorly reliable SWE results. SWE results correlated significantly with liver biopsy. Factors associated with reliable SWE results (i.e., no ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 70 publications
0
12
0
Order By: Relevance
“…The notion that the SCD must be considered was supported in another study, which suggested that the SCD could be used prospectively to identify cases that might require elevated push-pulse energy (Deng et al 2015). This notion was also supported in a previous study that included 188 individuals (Byenfeldt et al 2018). The ability to manage this factor (SCD) in ultrasound-based SWE represents a significant advantage over Fibro-Scan, which does not allow pressure.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The notion that the SCD must be considered was supported in another study, which suggested that the SCD could be used prospectively to identify cases that might require elevated push-pulse energy (Deng et al 2015). This notion was also supported in a previous study that included 188 individuals (Byenfeldt et al 2018). The ability to manage this factor (SCD) in ultrasound-based SWE represents a significant advantage over Fibro-Scan, which does not allow pressure.…”
Section: Discussionmentioning
confidence: 87%
“…These limiting factors were identified in a prospective study of 13,369 examinations (Castera et al 2010). Moreover, in an earlier study that included 188 individuals, increased subcutaneous fat was significantly associated with poor SWE reliability, with an OR as high as 3.08 (Byenfeldt et al 2018). The ARFI pulse has a "sweet spot" at a depth of 3À5 cm, where the pulse is focused.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, there are no studies examining the effect of food and water consumption on 2-dimensional SWE measurements using an Epiq 7 system (Koninklijke Philips NV, Best, the Netherlands). Other studies on interobserver and intraobserver reliability have focused on the reproducibility of elastographic measurements in fasting participants or the influence of age and body mass index, [8][9][10][11] whereas the secondary objective of this study was to evaluate the inter-and intra-reader variability of hepatic SWE measurements.…”
mentioning
confidence: 99%
“…Point shear wave elastography (pSWE) works by high-intensity US waves causing localized tissue displacement in a small region of interest (ROI) depending on the characteristics of the related tissue, resulting in the generation of shear waves that are detected by the US scanner with additional software capability, thereby indirectly quantifying LS, as the shear wave velocity (SWV) is proportional to the tissue elasticity [6][7][8]. The correlation between LS and fibrosis is well known, but is also influenced by several other pathologies, such as fatty infiltration, inflammation, cholestasis, congestion, and the patient's food/liquid intake before the exam [7,9]. The effects of these confounding factors have been documented by many studies using TE, and their influence on different SWE techniques is still being explored in different clinical processes and patient groups [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%